AGAIN ABOUT GENDER BASED VIOLENCE IN ROMANIA LEGISLATIVE MODIFICATIONS PROMULGATED ON MARCH 2012 - LAVINIA MIHAELA VLĂDILĂ (Challenges of the Knowledge Society)
The article continues our last year article, presented in the same conference, on the evolution of the legislation on domestic violence in Spain and in Romania. This new study shall approach only the legislative modifications of the Law No 217/2003 inserted in March 2012 after the shooting at “Perla” Hairdresser in Bucharest, which influenced not only the lives of those involved, but also legislative changes, as an attempt from the Government to offer a better protection for women, who are usually the victims of this type of violence. The present study is dedicated to these new modifications ad their social and legal impact.